Molecularly-porous ultrathin membranes for highly selective organic solvent nanofiltration - Huang, Tiefan; Moosa, Basem A.; Hoang, Phuong; Liu, Jiangtao; Chisca, Stefan; Zhang, Gengwu; AlYami, Mram; Khashab, Niveen M.; Nunes, Suzana P. (Nature communications, 2020)
Engineering membranes for molecular separation in organic solvents is still a big challenge. When the selectivity increases, the permeability tends to drastically decrease, increasing the energy demands for the separation process. Ideally, organic solvent nanofiltration membranes should be thin to enhance the permeant transport, have a well-tailored nanoporosity and high stability in harsh solvents. Here, we introduce a trianglamine macrocycle as a molecular building block for cross-linked membranes, prepared by facile interfacial polymerization, for high-performance selective separations. The membranes were prepared via a two-in-one strategy, enabled by the amine macrocycle, by simultaneously reducing the thickness of the thin-film layers (<10 nm) and introducing permanent intrinsic porosity within the membrane (6.3 Å). This translates into a superior separation performance for nanofiltration operation, both in polar and apolar solvents. The hyper-cross-linked network significantly improved the stability in various organic solvents, while the amine host macrocycle provided specific size and charge molecular recognition for selective guest molecules separation. By employing easily customized molecular hosts in ultrathin membranes, we can significantly tailor the selectivity on-demand without compromising the overall permeability of the system. Engineering thin membranes for molecular separation with well tailored nanoporosity and which can withstand harsh conditions is still a big challenge. Here, the authors introduce a trianglamine macrocycle as a molecular building block for cross-linked membranes, prepared by facile interfacial polymerization, for high performance selective separations.